Review on Adoption of Agroforestry Innovation by Farmers’ Social Forestry Program - Eva Fauziyah; Sanudin Sanudin (Balai Litbang Teknologi Agroforestry, Ciamis, 2021)
ABSTRACTAgroforestry can offer a balance between conservation and production in agricultural systems to provide socio-economic and ecological benefits. Agroforestry is a land use system that is applied in the social forestry program. The social forestry program aims to improve community welfare while still paying attention to environmental aspects and sociocultural dynamics. This paper aims to describe the adoption of agroforestry innovations in social forestry programs. The method used in this research is a literature study or review of various research results related to adoption and agroforestry innovation and social forestry from international journals, national journals, international proceedings, and national proceedings. Data analysis was carried out descriptively. The result of the study shows that agroforestry innovations in social forestry are needed by communities to increase benefits and reduce costs. Agroforestry innovation can be applied well in aspects of production/cultivation, such as the selection of plant species, arrangement of growing spaces or cropping patterns, maintenance, as well as in post-harvesting, marketing, and institutional aspects. So far, there have been many agroforestry innovations resulted from the agroforestry-based forest and land management, both innovations derived from local farmers' knowledge and innovations resulted from scientific researches or a combination of them. The agroforestry innovations that are most attractive to the community are agroforestry innovations along the cycle, which provide communities with longer opportunities to use the land. The main factors influencing the adoption of agroforestry innovations that must be considered are economic factors.Keywords: adoption, agroforestry, innovation, social forestry